Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Perumda Air Minum Pusat Kota Surakarta - Miftakul Jannah; Kartika Hendra Ts; Riana R Dewi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
The present study is aimed at examining the influence of user involvement, user training and education, support of top management, and personal technical ability on the performance of accounting information system (AIS) at city-owned water company of Surakarta, at which some employees were selected purposively as the sample AIS users based on the criterion that that they have a one-year minimum work experience. The results of multiple regression analysis show that user involvement, support of top management, and personal technical ability had positive influence in AIS performance. Conversely, user training and education had no influence on AIS performance.